Determination accuracy of analysis refractory materials by x-ray fluorescence - Janča, Martin; Šiler, Pavel; Opravil, Tomáš; Kotrla, Jan (IOP Publishing, 2018)
This work was focused on the finding of the right way how to analyze refractory materials by X-ray fluorescence. This method can provide accurate results which can be easily repeated, what is the reason why this method is commonly used in industry. Using of the fluorescent spectrometric analysis comes with one issue, which is the presence of many distorting interferences. From this particular reason it is necessary to identify these interferences and then find the ideal solution for their elimination. The choosing of the right method of sample preparation is basic point for making of well analyze results. The differences are shown on the refractory materials samples. All the values were compared according to standards compositions. In this case we compare different conditions of measurement, under air and vacuum. And different preparation form in powder or fusion into pearl.

This work was focused on the finding of the right way how to analyze refractory materials by X-ray fluorescence. This method can provide accurate results which can be easily repeated, what is the reason why this method is commonly used in industry. Using of the fluorescent spectrometric analysis comes with one issue, which is the presence of many distorting interferences. From this particular reason it is necessary to identify these interferences and then find the ideal solution for their elimination. The choosing of the right method of sample preparation is basic point for making of well analyze results. The differences are shown on the refractory materials samples. All the values were compared according to standards compositions. In this case we compare different conditions of measurement, under air and vacuum. And different preparation form in powder or fusion into pearl.
Determination accuracy of analysis refractory materials by x-ray fluorescence
Keywords: X-ray fluorescence; refractory; fusion; X-ray fluorescence; refractory; fusion